Liberation thinnings in logged-over forests - Sist, P.; Abdurachman (1998)
One of the objectives of the STREK project was to propose silvicultural methods able to increase forest production, especially in logged-over areas, The area RKL 1 which was logged 15 years ago was the most suitable zone to implement those trials. This study aims to describe the silvicultural treatments undertaken in RKL 1. Two different treatments were applied in addition to the control: the first treatment was a liberation thinning carried out systematically in the plot with a removal of 30% of the basal area involving the non-commercial species with dbh = 20 cm. The second silvicultural treatment was a two-fold intervention: (i) a liberation thinning focused around selected potential crop trees (PCT) characterised by an extraction of non-commercial species with dbh = 20 cm located within a circle of a constant 10 m diameter centred on the PCT; and (ii) an extraction of the same non-commercial species group with dbh = 40 cm outside the 10 m circles. The efficiency of the arboricide on the trees three years after treatment is given.